IMPLEMENTATION OF SELF-TUNING CONTROLLER TO AN AIR HEATING PROCESS - Ab Ghani, Mohd Ruddin (1993)
Extended horizon and k-incremental self-tuning controllers were implemented using a microcomputer on a laboratory scale air heating process. The performance of these controllers is evaluated and compared with the digital PID controllers. The results obtained indicates that the self-tuning controllers could improve the performance of the process significantly compared to the digital PID controller.